Towards re-conceptualising and measuring brand identity in services: a consumer perspective - Pareek, Vandana (The University of Edinburgh, 2015)
This thesis focuses on conceptualizing and measuring brand identity in services. The lack of a wider-accepted measure of brand identity is surprising given that it a) provides meaning to the brand, makes it unique and communicates what the brand stands for (Rosengren et al., 2010), and b) is the driver of one of the four principal dimensions of brand equity, namely, brand association (Keller, 1993). Despite its acknowledged importance, brand identity measurement has received remarkably little attention, and efforts to develop a valid and comprehensive measure have been limited. While prior work on brand identity has proposed some conceptual models highlighting different facets that contribute to brand identity development, the majority of these models have not been subjected to empirical testing. This raises concerns over their robustness and validity. More importantly, the applicability of these models to a service context is not clear. For instance, the role of consumers, who participate in the service production process and interact frequently with the service providers, is hardly considered in the prior frameworks. In summary, the dearth of research studies accounting for the consumer perspective of brand identity, along with the lack of a valid and comprehensive scale to measure service brand identity, motivated this research. This thesis thus aims to, first, review and refine the concept of brand identity to account for the consumer perspective of this construct and then develop a multidimensional scale to measure service brand identity and identify its key dimensions. To fulfill the research aims, Churchill‟s (1979) paradigm was followed in conjunction with DeVellis (2003) and other scale development studies (Brakus et al., 2009; Lundstorm & Lamont, 1976). This thesis employed both qualitative and quantitative research methods to achieve the research aims. Qualitative research was undertaken to gain additional insights into the construct (e.g. consumer perspective) and to generate and purify the initial scale items. Quantitative methods were then adopted to validate and establish the final scale. Guided by the aforementioned research design, this thesis developed a service brand identity (SBI) scale consisting of five dimensions labelled: process identity, organization identity, servicescape identity, symbolic identity and communication identity. The analysis confirms that the scale is reliable, valid, and parsimonious. Further, the scale application is demonstrated by assessing and empirically establishing the association between service brand identity and brand trust and loyalty. The results support the proposition that the consumer perspective is important in understanding and developing brand identity in a service context. Relatedly, it is also shown that service elements, such as the servicescape and service process, play a key role in developing a strong brand identity for services. The key contribution of this study is the development of a psychometrically valid and reliable scale. This research extends the literature on brand identity (Upshaw, 1995; Aaker, 1996; De Chernatony, 1999; Kapferer, 2000; Burmann et al., 2009; da Silveira et al., 2013) to include the service domain which has to date not received much research attention in branding. It proposes and empirically establishes two new dimensions of service brand identity (Process Identity and Servicescape Identity) which have not been highlighted in extant brand identity literature. In addition to this, this thesis provides a much-needed consumer perspective on brand identity and its components, thereby responding to calls for more research on marketing constructs to account for the consumer perspective (Rust, 1988; Payne et al., 2009; Arnould et al., 2006). In this regard, this study is among the first to empirically link consumer-based variables to a specific brand identity scale.
Keywords: brand identity; services marketing; scale development